Synthesis and Characterization of Pure Metastable g-Manganese Sulfide Microsphere at Low Temperature by Wet Chemical Technique - Veeramanik, T.; Rajendran2, K.; Sambath1, K. (Asian Journal of Chemistry, 2013)
In the present work, pure metastable g-manganese sulfide (g-MnS) microspheres have been synthesized in a controlled manner by varying the refluxing temperature of the solution using wet-chemical route. The g-MnS particles has been synthesized by using manganese acetate [Mn(CH3COO)2] and thioacetamide (CH3CSNH2) in aqueous solution. The prepared g-MnS microsphere has been characterized by X-ray diffraction, scanning electron microscope, UV-visible absorbance and photoluminescence. X-ray diffraction results show that as-prepared MnS microstructures exhibit tetrahedrally coordinated g-MnS wurtzite structure. The average crystallite size and specific surface area have been calculated from the XRD data. The morphological changes of the prepared g-MnS microspheres have been investigated. The EDAX analysis indicates the purity of as-prepared sample. UV-visible optical spectroscopy study has been carried out to determine the band gap energy of g-MnS particles. The room temperature photoluminescence spectrum exhibits a blue emission peak at around 440 nm.